Studi Tentang Penetapan Tersangka Dalam Kasus Prostitusi Online - Annisa Fujiyanti; John Dirk Pasalbessy; Erwin Ubwarin (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The practice of temporary sexual intercourse, which is more or less carried out with anyone, for monetary compensation. The three main elements in the practice of prostitution are: payment, promiscuity and emotional indifference in this case the suspect based on Law No. 21 of 2007 on online prostitution named vika who lent a room to prostitutes but he did not know that it would be used for prostitution in his room.Purposes of the Research: The purpose of this paper is to find out the evidence used in determining the suspect in online prostitution and the role in providing rooms to become a suspect. Methods of the Research: The method used is empirical juridical research. This type of research is descriptive-analytic. Data obtained From the field data used in this study, primary data and secondary data, data collection techniques are through interviews and qualitative data analysis.Results of the Research: The use of medical approval as evidence of decision Number 114/Pdt.G/2020/PN Bjm was not carried out thoroughly so that it resulted in material and immaterial losses. Factors that influence the use of medical consent as evidence include; lack of patient knowledge, answering patient doubts, confirming procedures in laws and regulations, proving doctors in the feasibility of doing something related to medical work.